Expectations, Credibility and Exchange Rate Dynamics: the Case of France 1922-1930 - Luisa Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1991)
The behavior of French economy in the 1920s rapresents a very interesting episode, wich attracted considerable analytical interest among the contemporaneous and, more recently, among aconomists and historians.
Keywords: 330